Interfacial energy of copper clusters in Fe-Si-B-Nb-Cu alloys. (15th March 2019) - Jha, Rajesh; Diercks, David R.; Chakraborti, Nirupam; Stebner, Aaron P.; Ciobanu, Cristian V.
Abstract: Using a combination of numerical simulations and atom-probe tomography experiments, we determine the interfacial energy of Cu nanocrystals precipitated within the amorphous matrix of FINEMET (molar composition Fe72.89 Si16.21 B6.90 Nb3 Cu1 ). Specifically, we use the Langer-Schwartz model implemented in the software Thermocalc to carry out parametric simulations of growth and coarsening of Cu clusters for different interface energies. We have carried out atom-probe tomography (APT) experiments to determine the interface energy as the value for which the simulated particle size distribution best matches the experimental data. This combination of APT and precipitation modeling can be applied to other nanocrystals precipitated within amorphous matrices. Graphical abstract: Description: Cu cluster size distributions simulated for different values of the interface energy γ (curves), compared with the distribution obtained from APT (blue histogram). Unlabelled Image